Porous Titanium Wedges in Revision First Metatarsophalangeal Arthrodesis. Issue 1 (January 2022) - Noble, David M.; Small, Benjamin; Cooper, M. Truitt; Park, Joseph S.; Perumal, Venkat
Category: Midfoot/Forefoot; Other Introduction/Purpose: First metatarsophalangeal (MTP) arthrodesis is a common procedure for hallux MTP pathology. In the setting of prior procedures with resultant bone loss, porous titanium wedges provide an alternative to allograft or autograft. The purpose of this study was to report clinical and radiographic outcomes achieved with titanium wedges used in 1st MTP arthrodesis in a revision setting. Methods: A retrospective analysis was performed in 10 patients (mean age 65.8) with prior 1st MTP procedures who underwent 1st MTP arthrodesis with use of porous titanium wedges from February 2014 to March 2020. Outcomes were assessed using both clinical (Visual Analogue Scale, Foot and Ankle Ability Measure, Mental Health Continuum Short Form, 36-Item Short Form Survey, need for revision) and radiographic parameters. Patients were followed from a minimum of 6 months up to 6 years (mean 31.4 months). Results: Average Foot and Ankle Ability Measure (FAAM) score was 91.1 +/- 14.7 (75.1 +/- 5.3 FAAM Activities of Daily Living; 17.9 +/- 9.9 FAAM Sports). Average pain visual analogue scale was 1.9 +/- 1.7. Average Mental Health Continuum-short form score was 34.2 +/- 8.5. Postoperative computed tomography (CT) imaging demonstrated lack of osseous integration in two of six CT scans obtained. Four patients underwent subsequent revision procedures, 3 for hardware prominence and 1 for failure of fusion. Conclusion: To our knowledge, these data represent the first reported clinical and radiographic outcomes in patients undergoing revision 1st MTP arthrodesis with use of porous titanium wedges. Further research should focus on comparative data with other commonly performed operative techniques.